FAMILY BUSINESS DEVELOPMENT IN THE REPUBLIC OF UZBEKISTAN: FEATURES AND CHALLENGES - Karajanova, Roza; Rakhimboev, Muzaffar (Innovative Development in Educational Activities, 2023)
The article is mainly about the development of family business in the Republic of Uzbekistan. A brief historical perspective on the development of entrepreneurship, the current state, some features of a family business abroad, the main difficulties and opportunities has been provided by the state. Family businesses have a long-standing history in Uzbekistan, with close-knit relationships among family members being a key feature. However, they also face challenges such as limited access to funding and a lack of formalized business structures. The transition to a market economy has also formed new challenges. Nevertheless, family businesses remain to play a significant role in the country’s economy, and with the right support, they have the potential to drive growth and create new opportunities.